Evaluating an intervention to reduce fear of falling and associated activity restriction in elderly persons: design of a randomised controlled trial [ISRCTN43792817] - van Eijk JThM; van Haastregt JCM; Zijlstra GAR; Kempen GIJM (BMC, 2005)
Abstract Background Fear of falling and associated activity restriction is common in older persons living in the community. Adverse consequences of fear of falling and associated activity restriction, like functional decline and falls, may have a major impact on physical, mental and social functioning of these persons. This paper presents the design of a trial evaluating a cognitive behavioural group intervention to reduce fear of falling and associated activity restriction in older persons living in the community. Methods/design A two-group randomised controlled trial was developed to evaluate the intervention. Persons 70 years of age or over and still living in the community were eligible for study if they experienced at least some fear of falling and associated activity restriction. A random community sample of elderly people was screened for eligibility; those eligible for study were measured at baseline and were subsequently allocated to the intervention or control group. Follow-up measurements were carried out directly after the intervention period, and then at six months and 12 months after the intervention. People allocated to the intervention group were invited to participate in eight weekly sessions of two hours each and a booster session. This booster session was conducted before the follow-up measurement at six months after the intervention. People allocated to the control group received no intervention as a result of this trial. Both an effect evaluation and a process evaluation were performed. The primary outcome measures of the effect evaluation are fear of falling, avoidance of activity due to fear of falling, and daily activity. The secondary outcome measures are perceived general health, self-rated life satisfaction, activities of daily life, feelings of anxiety, symptoms of depression, social support interactions, feelings of loneliness, falls, perceived consequences of falling, and perceived risk of falling. The outcomes of the process evaluation comprise the performance of the intervention according to protocol, the attendance and adherence of participants, and the participants' and facilitators' opinion about the intervention. Data of the effect evaluation will be analysed according the intention-to-treat and on-treatment principle. Data of the process evaluation will be analysed using descriptive techniques.